TEACHING SELF-AWARENESS AND SELF-REGULATION TECHNIQUES TO A CHILD WITH AUTISM SPECTUM DISORDER - Kontogianni, Maria; Nanou, Andromachi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Self-awareness and self-regulation yoga techniques lead to stress management, reducing anxiety and well-being of individuals with Autism Spectrum Disorders. The current study seeks to investigate the degree of the autonomous involvement of an 11-year-old girl with Autism Spectrum Disorder in the self-awareness and self-regulation yoga exercises. The research was designed as an educational intervention. The intervention was applied once a week for 3 months, and took place at the sensory room of “School for all: Tokei Maru” at Include in Thessaloniki. Research diaries and observation protocols, by participant and external observers, were used for data collection before, during and after the intervention. According to the research findings, girl’s degree and quality of involvement improved during the intervention, so that she managed to use specific techniques autonomously. Research findings cannot be generalized, but they are encouraging in developing effective self-awareness and self-regulation programs for children with Autism Spectrum Disorder in future research.